Design and fabrication of a cost effective solar air heater for Bangladesh - Wazed, M.A.; Nukman, Y.; Islam, M.T. (Elsevier, 2010)
In this research, a solar air heater is designed, fabricated and its performance is assessed in the perspective of an emerging/developing country with a huge energy demand like Bangladesh. The winter season (mid-November-mid-February) of the country characterizes by low temperatures, cool air blowing from the west or northwest, clear sky and meager rainfall. Minimum temperature in the extreme northwest in late December and early January sometimes reaches 3 degrees C and day length is about 10 h. The shortness of winter days can be compensated by reducing the heat loss during long nights. The solar air heater is constructed to prevent as much heat loss as possible. In other words, the heating of air is accomplished by maximizing light gain and minimizing heat loss. It is observed that the fabricated solar air heater is working efficiently. The maximum room temperature and the temperature difference from ambient are 45.5 degrees C and 12.25 degrees C for forced circulation and 41.75 degrees C and 8.5 degrees C for natural circulation respectively. The experimental outlet temperatures have been compared with that of theoretical values. Due to its low-cost and simple technology, it is affordable in all aspects, viz, of cost, operation and maintenance by the typical people of Bangladesh. (C) 2010 Elsevier Ltd. All rights reserved.